Pengaruh promosi kesehatan menggunakan media leaflet terhadap pengetahuan masyarakat tentang diabetes melitus tipe-2 di Puskesmas tahun 2024 - Crystandy, Muhammad; Siregar, Dian Maya Sari; Nisa, Khatrun (Jurnal Kesmas Prima Indonesia, 2024)
Introduction: Diabetes Mellitus is a disease that can kill a person slowly and still occurs in Indonesia, including in one of the community health centers in North Aceh Regency. Indonesia is in 7th place in the top 10 countries with a total of 10.7 million Diabetes Mellitus sufferers.: this research is to determine the effect of health promotion using leaflet media on public knowledge about Type 2 Diabetes Mellitus at the Lhoksukon Health Center, North Aceh in 2024. Type of research: this uses quantitative research with Pre-Experimental Design with a One Group Pretest-Posttest research design . The population in this study were people aged >40 years who were at risk of developing type 2 diabetes mellitus with a sample size of 15 respondents using the purposive sampling technique. Data analysis used univariate and bivariate analysis with the Normality Test and Paired Sample T-Test. The results of the analysis show that the respondent's answer value or mean for pretest knowledge is 7.33, for posttest knowledge it is 10.60. The probability value of knowledge before and after being given health promotion using leaflet media is (sig-p) 0.000 < 0.05. This means that there is an influence of leaflet media on public knowledge about Type 2 Diabetes Mellitus. The conclusion of this research is that there is an influence of leaflet media on public knowledge about Type 2 Diabetes Mellitus at the North Aceh Lhoksukon Community Health Center in 2023, with a sig-p value = 0.000. . It is recommended that local health centers utilize leaflets in selecting health promotion media